Employment of Fe3O4/Fe2TiO5/TiO2 Composite Made Using Ilmenite for Elimination of Methylene Blue - Himasha Gunathilaka; Charitha Thambiliyagodage (ChemEngineering)
A novel material was created from natural ilmenite sand, and methylene blue (MB) was used to test the material’s capacity to remove colors from wastewater. The material was synthesized by neutralizing the acid leachate obtained by Ilmenite sand digestion, followed by drying at 180 °C. It was characterized by XRD, Raman, TEM, SEM, XPS, XRF, and BET techniques. The crystal nature of the composite is Fe3O4/Fe2TiO5/TiO2. The surface area, average pore size and total pore volume of the composite are 292.18 m2/g, 1.53 nm, and 0.202 cc/g, respectively. At pH 10, 10 mg/L MB, and 10 mg of the material resulted in a maximum adsorption capacity of 24.573 mg/g. Using 5 mg/L increments, the dye concentration was adjusted between 10 and 25 mg/L, yielding equilibrium adsorption capacities of 24.573, 31.012, 41.443, and 52.259 mg/g with 10, 15, 20, and 25 mg/L, respectively. The greatest adsorbent capacity of 24.573 mg/g was achieved with 10 mg of the adsorbent and 10 mg/L MB. The adsorbent dosage ranged from 10, 25, 45, 65, and 100 mg. MB was adsorbed via pseudo-second-order kinetics with an adsorption capacity of 24.863 mg/g. The intraparticle diffusion model showed that MB adsorption occurs in three stages, with intra-particle diffusion constants of 1.50, 2.71, 3.38, and 4.41 g/mg min1/2. Adsorption followed the Langmuir isotherm model. The obtained thermodynamic parameters ΔG, ΔH, and ΔS were −27.5521 kJ/mol at 298 K, 2.571 kJ/mol, and 0.101 kJ/mol, respectively. Regeneration studies of the adsorbent were carried out for five cycles, indicating some activity loss after each cycle.